Oratory in Native North America - Clements, William M., 1945- (Book collections on Project MUSE., 2002)
Publisher description: In Euroamerican annals of contact with Native Americans, Indians have consistently been portrayed as master orators who demonstrate natural eloquence during treaty negotiations, councils, and religious ceremonies. Esteemed by early European commentators more than indigenous storytelling, oratory was in fact a way of establishing self-worth among Native Americans, and might even be viewed as their supreme literary achievement. William Clements now explores the reasons for the acclaim given to Native oratory. He examines in detail a wide range of source material representing cultures throughout North America, analyzing speeches made by Natives as recorded by whites, such as observations of treaty negotiations, accounts by travelers, missionaries' reports, captivity narratives, and soldiers' memoirs. Here is a rich documentation of oratory dating from the earliest records: Benjamin Franklin's publication of treaty proceedings with the Six Nations of the Iroquois; the travel narratives of John Lawson, who visited Carolina Indians in the early 1700s; accounts of Jesuit missionary Pierre De Smet, who evangelized to Northern Plains Indians in the nineteenth century; and much more. The book also includes full texts of several orations. These texts are comprehensive documents that report not only the contents of the speeches but the entirety of the delivery: the textures, situations, and contexts that constitute oratorical events. While there are valid concerns about the reliability of early recorded oratory given the prejudices of those recording them, Clements points out that we must learn what we can from that record. He extends the thread unwoven in his earlier study Native American Verbal Art to show that the long history of textualization of American Indian oral performance offers much that can reward the reader willing to scrutinize the entirety of the texts. By focusing on this one genre of verbal art, he shows us ways in which the sources are-and are not-valuable and what we must do to ascertain their value. Oratory in Native North America is a panoramic work that introduces readers to a vast history of Native speech while recognizing the limitations in premodern reporting. By guiding us through this labyrinth, Clements shows that with understanding we can gain significant insight not only into Native American culture but also into a rich storehouse of language and performance art.